2013
DOI: 10.1080/10978526.2013.780453
|View full text |Cite
|
Sign up to set email alerts
|

Insights on International Franchising: Entry Mode Decision

Abstract: Despite the substantive importance of Latin America for foreign investors, the academic attention paid to this region continues to be limited. To cover this gap, this study examines how a number of franchise chain characteristics and market conditions may have an influence on the entry options that global franchisors have when seeking to expand their business in Latin America. Results conclude that the level of a host's country uncertainty avoidance, masculinity, economic development, economic potential, corru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 63 publications
0
21
0
1
Order By: Relevance
“…In the past, this region has shown a high level of risk for investment because of great economic and political instability (Baena, 2013). Nowadays, however, even though there is still some risk, the long-term potential for growth and profitability is increasing.…”
Section: Implications For Practitionersmentioning
confidence: 99%
“…In the past, this region has shown a high level of risk for investment because of great economic and political instability (Baena, 2013). Nowadays, however, even though there is still some risk, the long-term potential for growth and profitability is increasing.…”
Section: Implications For Practitionersmentioning
confidence: 99%
“…The usefulness of this magazine is that it annually reports data on Mexican franchises and has been used as a secondary source by other authors (Alba, 2010; Fable & Welch, 1998; Lafontaine & Oxley, 2001). Likewise, these sources of information have been used as a source of data for research in other countries (Alon, 2001; Baena, 2013; Castrogiovanni et al, 2006b; Shane, 1996b). Because the information reported in the Entrepreneur 500 franquicias magazine did not include data on franchised units, it was necessary to obtain these values by consulting the website of the Mexican Franchise Association, the website of each franchisor and the electronic specialized journals in franchising as top http://franquicias.com, comprafranquicia.mx, and http://100franquicias.com.mx.…”
Section: Methodsmentioning
confidence: 99%
“…The empirical literature on the choice of governance modes by franchisors is relatively small. A few studies (Alon, 2006;Baena, 2013;Brookes and Roper, 2011) have examined factors affecting the franchisor's choice of specific governance modes such as master franchising. Recent reviews of the literature (Jell-Ojobor and Windsperger, 2014;Rosado-Serrano et al, 2018) identified 18 studies pertaining to franchise governance modes.…”
Section: Modes Of Governance For Market Entry 909mentioning
confidence: 99%